Analisis Implementasi Pemeriksaan USG dalam Antenatal Care (ANC) di Puskesmas Kota Semarang - Aulia Ulfah Mutiara Dewi; Martha Irene Kartasurya; Cahya Tri Purnami (Universitas Malahayati, 2026)
ABSTRACT Background: The disparity in maternal mortality rates (MMR) between developed countries and low-middle income countries was very large, including in Indonesia. One of the differences between the two was the ultrasound examination that had been used for a long time in developed countries. Semarang was one of the capital city that had implemented ultrasound examination as one of the examinations for pregnant women since 2022. To determine the implementation of ultrasound examination as an early detection of pregnancy complications at primary health care (PHC) in Semarang. Qualitative research with a case study research design. Research data were obtained through interviews, observations, and other documents collected in the period September-December 2024 at 4 PHCs in Semarang. Ultrasound examinations at PHCs were good, but there were several examination indicators that had not been carried out optimally. Two factors that influence its implementation were human resources (HR) and infrastructure. Constraints on HR include uneven distribution, mutations of trained doctors, and varying training curricula. Meanwhile, the constraints encountered in infrastructure were technical constraints on ultrasound equipment, the response of the equipment provider vendor, and the ultrasound room that were not yet up to standard. Improvement efforts were needed in the aspects of human resources and infrastructure in order to improve the quality of USG examination services at PHCs in Semarang. Keywords: Obstetric Ultrasound, Antenatal Care, Primary Health Care. ABSTRAK Ketimpangan angka kematian ibu (AKI) antara negara maju dengan negara berkembang sangat besar, termasuk di Indonesia. Salah satu perbedaan keduanya adalah pemeriksaan USG telah digunakan sejak lama di negara maju. Kota Semarang merupakan salah satu ibu kota yang telah menerapkan pemeriksaan USG sebagai salah satu pemeriksaan bagi ibu hamil sejak 2022. Untuk mengetahui implementasi pemeriksaan USG sebagai deteksi sebagai deteksi dini komplikasi kehamilan di Puskesmas Kota Semarang. Penelitian kualitatif dengan desain penelitian studi kasus. Data penelitian diperoleh melalui wawancara, observasi, dan dokumen lainnya yang dikumpulkan pada periode September-Desember 2024 pada 4 puskesmas di Kota Semarang. Pemeriksaan USG pada ANC di Puskesmas Kota Semarang sudah baik, namun terdapat beberapa indikator pemeriksaan yang belum dijalankan secara optimal. Dua faktor yang memengaruhi pelaksanaannya adalah sumber daya manusia (SDM) dan sarana prasarana. Kendala pada SDM meliputi distribusi yang belum merata, mutasi terhadap dokter yang terlatih, dan kurikulum pelatihan yang bervariasi. Sedangkan kendala yang ditemui pada sarana prasarana adalah kendala teknis alat USG, respon vendor penyedia alat, dan ruang USG yang belum sesuai standar.Diperlukan upaya perbaikan pada aspek SDM dan sarana prasarana demi meningkatkan kualitas pelayanan pemeriksaan USG pada ANC di Puskesmas Kota Semarang. Kata Kunci: Pemeriksaan USG, ANC, Puskesmas.